Epidemiology of extended-spectrum beta-lactamase producing Enterobacteriaceae in Qatar: A 3-year hospital-based study - Alsamawi, Musaed; Joudeh, Anwar I.; Eldeeb, Yaseer; Al-Dahshan, Ayman; Khan, Fahmi; Ghadban, Wissam; Almaslamani, Muna; Alkhal, Abdulatif (Frontiers in Antibiotics, 2022)
Abstract Background: The incidence of ESBL infections is exponentially increasing with variable prevalence among geographical areas and treatment settings. Identifying local prevalence rate and patient-related factors will help in earlier recognition and initiation of appropriate antibiotics treatment of patients with ESBL infections. Methods: Retrospective analysis of all positive cultures for ESBL producing Enterobacteriaceae collected in Al-Khor hospital from January 2010 to December 2012. ESBL bacterial isolates reported as cephalosporin-resistant or ESBL using the automated VITEK Gram-Negative Susceptibility System with cards GNS 206 and 121 were screened for ESBL detection using the disk diffusion method in keeping with the Clinical and Laboratory Standards Institute. Both descriptive and analytic statistics were applied when appropriate, and univariate analysis was used to identify significant factors. Results: Most of the ESBL-producing bacterial isolates were E. coli, which were also resistant to other classes of antimicrobials. Meropenem, amikacin and nitrofurantoin retained good coverage to most isolates. Klebsiella pneumonia infection was most likely associated with diabetes mellitus (p =0.004), hospital-acquired infection (p =0.046) and with more severe infection (p =0.006). ESBL associated hospital-acquired infections were more likely to occur in older patients, those with comorbidities and with invasive device use. ESBL-associated urinary tract infections were most commonly community-acquired while ESBL associated respiratory tract infections were acquired from hospitals (‎p =<0.001). Factors associated with mortality include treatment in the ICU (OR 104.8 [9.82-1116.96] p<0.001), sepsis/septic shock (OR 20.80 (5.68-76.12) p <0.001), hospital-acquired infections (OR 8.80 [1.88-41.16] p =0.006) and bacteremia (OR 8.80 [1.63-47.5] p=0.013). Conclusion: Multiple risk factors were associated with ESBL infections both in the community and hospital setting. Prediction tools are needed to improve the protocol of appropriate empiric antibiotic selection while preserving antimicrobial stewardship recommendations.